(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Crop improvement as an innovation in plant breeding and genetics requires the deployment of new allelic variants. To achieve this, different types of genome modifications are recently in used, such as ZFN, TALEN, MN, and CRISPR/Cas genome editing systems. However, off-target mutations are the major concerned associated with the use of ZFNs for genome editing. As such, the creation of obligate heterodimeric ZFN architectures that rely on a charge-charge repulsion to prevent unwanted homodimerization of the FokI cleavage domain has been in used to enhance ZFNs specificity. TALENs offer distinct advantages for genome editing compared to ZFNs; it has higher specificity and reduced toxicity compared to some ZFNs and no selection or directed evolution is necessary to engineer TALE arrays. Compared with ZFNs and TALENs, the CRISPR/Cas system is characterized by its simplicity, efficiency, and low cost, and by its ability to target multiple genes. Due to these characteristic features, CRISPR/Cas9 has been rapidly exploited in plants and may be an effective solution to a variety of problems in plant breeding. Conclusively, the CRISPR/Cas9 system provides a valuable platform for generating mutants with high frequency in polyploid crops and very useful for post-transcriptional control of gene expression as well as the simultaneous editing of multiple target sites.